Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Get quick and reliable solutions to your questions from a community of experienced experts on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
1x + 3y = 5
2x - 3y = 1
3x = 6
3 3
x = 2
2(2) - 3y = 1
4 - 3y = 1
-4 -4
-3y = -3
-3 -3
y = 1
(x, y) = (2, 1)
2x - 3y = 1
3x = 6
3 3
x = 2
2(2) - 3y = 1
4 - 3y = 1
-4 -4
-3y = -3
-3 -3
y = 1
(x, y) = (2, 1)
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.